A formulação e a execução das estratégias na educação do RS: artefato baseado no BSC pode contribuir na escolha, no alinhamento e na execução das estratégias - Rosa, José Paulo da (Universidade do Vale do Rio dos Sinos, 2025)
The thesis discusses the strategy for education in the state of Rio Grande do Sul, from the government, the state department of education, the regional education coordinators and state schools. Using Design Science Research as a research method, it proposes an artifact that helps solve the problem. The problem has to do with the poor results of Brazilian education and the state of Rio Grande do Sul in particular. Indicators are presented that demonstrate the low performance of students. The proposed research question was: how can strategies for education in Rio Grande do Sul be better deployed, executed and monitored? In the literature review, it presents an analysis of strategy and education management and seeks references in the work of Robert Kaplan and David Norton on Balanced Scorecard for the solution presented. The research was carried out with a representative of the state government, with the current secretary of education, with the previous secretary of education, with a regional education coordinator and with a state school director. As a result of this research, a lack of harmony between the different levels of government was demonstrated, regarding their strategies for education. Based on the elements collected and following the Design Science Research (DSR) methodology, the artifact was developed, tested with a focus group and presented at the end. The artifact is a tool based on the Balanced Scorecard, being a cloud system that can be accessed via desktop, tablet or cell phone and allows the state government, State Department of Education, Regional Education Coordinators and state schools to prepare their plans, execute and monitor performance, in a connected and aligned way at its different levels. This artifact will be available to interested governments, both at state and municipal levels, contributing to better planning and execution of education strategies.
Keywords: Gestão da educação; Planejamento estratégico; Estratégias educacionais; Education management; Strategic planning; Educational strategies; ACCNPQ::Ciências Sociais Aplicadas::Administração